Imagens do êxtase : relações sociotécnicas entre o audiovisual e os esportes de ação e aventura na natureza - Manea, Gilberto Caetano (2018)
This dissertation presents as a piece of epistemological inquiry the modes of film narrative enunciation of the audiovisual production of sports considered "radical". The research deals specifically with the ecstatic figurations as a translation of the relations between technical images and modes of agency and operation of audiovisual language in the practice of alternative sports that defy the forces of nature. This study is performed according to the essayistic method of thought images found doubly in Walter Benjamin (denkbilder) and Gilles Deleuze, experienced as an exercise in creative critical film writing on the issues of film narrative enunciation (representations of body movement) of action sports, in parallel lines of reflection (symmetrical anthropology) from the beginnings of the invention of the cinema and the contemporary video sphere.